Global review of zucchini (Cucurbita pepo) pollination: research approaches, distribution of pollinators and knowledge gaps - Isabelle Cristina Santos Magalhães; Gerlayne Teixeira de Souza; Marcelo da Rocha Souza; Isabella Hevely Silva Torquato; André Maurício Melo dos Santos; Cibele Cardoso Castro (Revista Ciência Agronômica)
ABSTRACT Crop pollination is indispensable for global food security. Studies that summarize the knowledge about pollination of specific crops are relevant because they identify the distribution of pollinators, guide pollinator management and conservation policies, and highlight knowledge gaps. Zucchini is cultivated in several countries, and its production is essentially dependent on pollinators. We aimed to integrate global data on zucchini pollination and answer the following questions: (1) What are the topics addressed and what are the trends of the results? (2) Which organisms pollinate zucchini, and how are they globally distributed? (3) What are the knowledge gaps? We performed a systematic literature review, built a network of countries and pollinators, and compared data on the efficiency of specific pollinators. Studies were conducted in 16 countries. Most studies investigated the frequency and diversity of floral visitors. Other approaches were discussed. Zucchini flowers fed 116 species of pollinators, especially bees. Six countries had almost exclusive groups of native pollinators. Apis, Bombus, and Peponapis were the most frequently recorded bees. Areas with high habitat diversity improve pollination. There was a significant difference in productivity when pollination was carried out by bees compared with pollination by Syrphidae. The main knowledge gaps are (1) the determination of which native, manageable pollinators are efficient for maximum zucchini production, (2) the investigation of how pollination influence fruit nutritional composition and seed quality, and (3) the identification of pollinators to the species level.